Spatial distribution of land use concentration and land-use efciency of the Kakodonga river basin, Assam - Bora, Rana; Krishnaiah, Y.V. (National Geographical Journal of India, 2021)
The Kakodonga river basin covers an area of about 1,113 km . The average maximum temperature is 0 0 28.5 C and the minimum temperature is 18.4 C. The average rainfall of the basin is 1766 mm. The present paper is an attempt to analyse spatially land-use concentration and land-use efciency of the Kakodonga river basin. For the preparation of thematic maps, Survey of India topographic sheets and IRS P6 LISS-III imagery (2011) data are used. The land-use categories data has been collected for three years (2012-2014) at the revenue circle level from the Economic and Statistical Department of Assam. To work out land-use concentration Bhatia's (1965) method was adopted. The major land-use categories are forest cover, area put under non-agricultural use, barren lands, permanent pastures, and other grazing lands, miscellaneous trees and groves, culturable wasteland, current fallow land, other fallow lands, and the net area sown. The land-use efciency has been worked out taking ve positive variables are net sown area, total irrigated area, area irrigated more than once, the intensity of irrigation, and intensity of crops.